The Temple Mount and Pre-Islamic Jerusalem between Judaism and Christianity - Aljaž Krajnc (Edinost in Dialog, 2023)
This paper presents the pre-Islamic Jews’ and Christians’ conception of Jerusalem, the Temple Mount and the Basilica of the Holy Sepulchre. The first part of the paper presents Jewish views of the Temple Mount, pointing out that Jews hoped, and still do, to rebuild the Temple, and that there was a widespread belief in rabbinic Judaism that in the centre of the Temple stood a stone called the šǝtiyyâ, which marked the centre of the world, and from which the world was created. The second part of the paper analyses the notion of the eternal desolation of the Temple Mount among Syriac Christians, which developed in close contact with rabbinic Judaism. The article shows that the Christian thesis on the eternal destruction of the Jewish Temple is closely related to the Christian critique of rabbinic Judaism as such and of religious practices of Jews. In the course of the development and construction of the Christian earthly Jerusalem, Christians developed a distinctive system of beliefs that integrated some of the characteristics that Jews ascribed to the Temple, including the belief in the Temple as the centre of the world. In the conclusion, the article sketches the basic tensions between Judaism and Christianity regarding the future of the Temple Mount at the beginning of the 7th century. When Muslims conquered Jerusalem and entered into the world of these tensions, they forever changed it through the deliberate use and refutation of Christian and Jewish belief in accordance with their own religious teachings.